An Analysis Of Shiite Interpretations Of The Qur’an From The Sunnite Perspective - Mohd Hasrul, Shuhari; Mohd Shaifulbahri, Abdullah; Mohd Safri, Ali (2018)
Majority of Muslims base their understanding of the Qur‟an on the interpretations of Ahl al-Sunnah wa al-Jama‟ah scholars because it is believed that their scholarly interpretations are the most accurate at helping Muslims to understand the Qur‟an correctly. However, the Shiite scholars‟ interpretations are different from the Sunnite versions. This study conducted a content analysis on some of the books written by the Shiite and Sunnite scholars and found that there are several interpretational differences. This article describes the irregularities found in the Shiite interpretations of the Qur‟anic verses from the Sunnite perspective. These irregularities exist because Shiite scholars tend to base their interpretations on the concept of the religious leadership, a main pillar of their faith.